Nursing care for the elderly with hypertensive peak in emergency (Research, Society and Development, 2024)
Introduction: The aging population and the increasing prevalence of systemic arterial hypertension among the elderly highlight the importance of prompt and adequate interventions to prevent serious complications. Objective: This study aims to synthesize evidence on nursing interventions, monitoring, and the impact of care strategies, focusing on hypertensive urgencies and emergencies. Materials and Methods: This is a literature review of studies published between 2014 and 2023 in the databases PubMed, LILACS, and SciELO, analyzing articles that address the management of hypertensive crises in the elderly. The selection of articles followed inclusion and exclusion criteria, organizing the data according to thematic categories. Results: The results show that nursing interventions, such as medication administration and continuous monitoring, are crucial for stabilizing blood pressure and preventing organ damage. Adherence to structured protocols improves clinical outcomes, reduces complications, and decreases hospitalizations. Additionally, patient education and ongoing training for healthcare professionals are essential. Final Considerations: It is concluded that the implementation of evidence-based care and clear protocols is essential for the effective management of hypertensive crises, with a need for further studies to validate and enhance interventions.